The construction of a new paradigm of educating: from singular to collective, reflections needed in pandemic times (Simbiótica. Revista Eletrônica, 2020)
This article aims to provide reflection, having as lens the practices used and developed during the pandemic period in which the AGENT COVID-19 spread in multiple directions shifting our daily lives, our routines, disincorporating ourselves from the world and establishing new languages, new behaviors imposing a new model of representation of the dimensions of reality. The synthesis attempted in this article could only be performed through a brief qualitative cartographic historiography committed to access to the force plan that responds to the transformation of the experience that offer us clues to walk in a beyond the science-implementation dichotomy following paths, implication in production processes, connection of networks or rhizomes. We conclude that we are not yet a new collective. We are individuals on our way to a group consciousness. For now, what's happening in this pandemic is that we all run under the awning of a bar because it's raining. Thus, the contribution of the pandemic, allows us to invent a new language, which leads us to establish a relationship with our territory and our culture in a fairer way, more connected with our nature, making an architectural design more compatible with our “topography”, with our culture, with the people of the place.Keywords: Pandemic; Covid-19; isolation; crisis.